2001
DOI: 10.1007/s00122-001-0551-3
|View full text |Cite
|
Sign up to set email alerts
|

The wheat γ-gliadin genes: characterization of ten new sequences and further understanding of γ-gliadin gene family structure

Abstract: Ten new wheat γ-gliadin gene sequences are reported and an analysis of γ-gliadin gene family structure is carried out using all known γ-gliadin sequences. The new sequences comprise four genomic clones with significantly more flanking DNA than previously reported, and six cDNA clones from a wheat endosperm EST project. Analysis of extended flanking DNA from the genomic clones indicates the limits of conservation of γ-gliadin DNA sequence that are similar to those previously found with other gliadin and gluteni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(60 citation statements)
references
References 29 publications
3
57
0
Order By: Relevance
“…There are from 25 to 150 copies of the genes that encode the α-gliadins, depending on the variety (Anderson and Greene 1997). The γ-gliadins and ω-gliadins are encoded by clusters of gene families, composed of 15-40 and 15-18 copies, respectively (Sabelli and Shewry 1991;Anderson et al 2001). Comparisons of amino acid sequences deduced from DNA sequences have demonstrated that α-and β-gliadins have similar sequences, leading to the proposal that they be combined, so that the gliadins would be subdivided into α, γ, and ω groups ( Fig.…”
Section: Primary Structures Of Gliadinsmentioning
confidence: 99%
“…There are from 25 to 150 copies of the genes that encode the α-gliadins, depending on the variety (Anderson and Greene 1997). The γ-gliadins and ω-gliadins are encoded by clusters of gene families, composed of 15-40 and 15-18 copies, respectively (Sabelli and Shewry 1991;Anderson et al 2001). Comparisons of amino acid sequences deduced from DNA sequences have demonstrated that α-and β-gliadins have similar sequences, leading to the proposal that they be combined, so that the gliadins would be subdivided into α, γ, and ω groups ( Fig.…”
Section: Primary Structures Of Gliadinsmentioning
confidence: 99%
“…Therefore, these three clones are probably pseudogenes, as do two other clones (Hn4 and Hn5) from hull-less barley [18]. So far, only two B-hordein pseudogenes have been reported in other barley accessions [10,17], but pseudogenes are very common in other cereal prolamin gene families, such as those in wheat and maize [22,[26][27][28][29][30][31][32].…”
Section: Pseudogenesmentioning
confidence: 94%
“…In this research, phylogenetic analysis was performed on γ-gliadin amino acid sequences to construct a cladogram using Triticeae representative amino acid sequences as controls. The repetitive regions of γ-gliadin consist of a long direct repeat and evolve rapidly, so they are not considered suitable for determining relatedness (Anderson et al, 2001). Therefore, the repetitive domains are not included here for constructing the cladogram.…”
Section: Phylogenetic Analysis Of the Dasypyrum γ-Gliadin Genesmentioning
confidence: 99%
“…The α-and β-subfamilies are clustered on the short arms of homologous group 6 chromosomes, while γ-and ω-subfamilies are located on the short arms of homologous group 1 chromosomes (Dubcovsky et al, 1997). The γ-gliadins have been considered to be the most ancient members of the wheat glutenin (Anderson et al, 2001). The molecular cloning and sequencing of these genes are helpful for better understanding the relationships of their structures and functions, and will provide vital information on gene evolution (Guo et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation